POTRET PELAKSANAN LAYANAN BIMBINGAN DAN KONSELING KARIR DI SEKOLAH MENENGAH PERTAMA - Hasrul, Hasrul; Habsyi, Irsan (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
Career guidance and counseling is a service provided to students that aims to help students adjust, understand the world of work, and be able to determine career choices and plan their careers. The purpose of this study was to describe the implementation of career guidance and counseling services that have been implemented by teachers in junior high schools. The research method used is descriptive/interpretive qualitative. This study was conducted at SMPN 13 Ternate City. The results of this study describe that in the implementation of career guidance and counseling services in schools, guidance and counseling teachers at SMPN 13 Ternate City have implemented it, but the implementation has not been carried out optimally in the form of a comprehensive guidance and counseling program. In addition, the time allocation given is not sufficient for the service process needed by students and the provision of facilities in the form of facilities and infrastructure is inadequate. Another finding is that there are many obstacles faced by guidance and counseling teachers in efforts to implement career guidance and counseling services in schools efficiently and effectively.